Analisis Pembelajaran Daring Kolaboratif pada Mata Kuliah Sistem Budaya dan Dinamika : Studi Kasus pada Mahasiswa Pendidikan Sejarah dan Sosiologi IKIP Budi Utomo dan Mahasiswa Pendidikan Sejarah Universitas Flores - Winin Maulidya Saffanah; Faizah Ulumi Firadausi; Maria Goretty Djandon (FKIP, Universitas Palangka Raya, 2023)
Pembelajaran daring kolaboratif (PDK) is initiated by Kementerian Pendidikan, Kebudayaan, Riset, dan Teknologi to accelerate online learning in higher education. This qualitative study explores the implementation of PDK in Pendidikan Sejarah dan Sosiologi IKIP Budi Utomo and Pendidikan Sejarah Universitas Flores in Sistem Budaya dan Dinamika course. The study employs interviews, observations, and document analysis to investigate the students' perceptions of the effectiveness of PDK in enhancing their learning outcomes and engagement. The findings of this study reveal that PDK was positively received by the students and was considered successful. However, some technical issues, such as network problems, created obstacles to the learning process. The students overcame these challenges by making an effort to listen and understand the course materials. This study highlights the potential benefits and challenges of using collaborative online learning in higher education. It shows that PDK can enhance students' learning outcomes and engagement by providing opportunities for peer collaboration, increased interaction between students in different place, and more contextual learning. However, technical issues can pose challenges to the learning process and require effort from both students and instructors to overcome them